Motivation In Second Language Acquisition; Primary Schools of Tanzania - Ibrahimu Kadau (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
Motivation is among the leading predictors of second language learning. This study investigated the influence of motivation on second language (English) acquisition in primary school students. The study used a qualitative research approach, with case study design as the strategy. The researcher employed purposive sampling to conduct interviews with three primary school English language teachers. Besides, documentary reviews were used to collect suitable data for the study. The findings indicated that motivation is a paramount factor for Second language acquisition (SLA), however, cultivation of motivation to primary school students is a hindrance to most teachers as capacity to use varied experience, student’s efforts, and the learning environment obscuring cultivation of effective motivation. In conclusion, for effective SLA, teachers should develop their skills at fostering motivation to SL learners.